(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the knowledge, attitude, and practice on dengue prevention in Dong Xuyen ward, Long Xuyen city, An Giang province in 2021. Methods: A cross-sectional study was conducted with a sample size of 350 people from 18/02/2021 to 30/03/2021. Results: The percentage of respondents with good knowledge, attitude and practices were 46.6%, 48.0% and 57.1% respectively.